PARTISIPASI LEMBAGA DESA ADAT DALAM PENANGANAN PENDUDUK PENDATANG DI KELURAHAN SUMERTA, DENPASAR - Alit Laksmiwati, Ida Ayu (PIRAMIDA; Vol. 2, No. 2 Desember 2006)
Abstract The growth of Balinese population is increasing. In 1980 ? 1990 period the population growth is 1,18 % a year. It is moving up to 1,26 % in 1990 ? 2000 period. During 1990 ? 2000, from the nine regencies/city in Bali, the population growth of Denpasar City is higher than other regencies even higher than population growth of Bali, with is constitutes 3,20 %. The influence factors of population growth is consist of natural increase ( includes the number of birth and death ) and social increase with migration. The Denpasar population growth is not depending on natural increase component ( The government of Denpasar City, 2001) The registration data of migrant in Denpasar influence positively to the population growth. It means the number of in migrant is higher than the number of out migrant. In 1999 the number of net migrant in Denpasar is 5,448, 6,253 in 2000, and about 19,589 in 2001. The increase of migrant from 2000 to 2001 are about three times more. During this period the institution which has an authority to do the population registration at Denpasar City is the official staff of district (desa/kelurahan). However since several years, the participation of the traditional institution (banjar/desapakraman) has been involved with the establishment of some rules of Denpasar City, that is The Denpasar Regency?s Rule No : 5 year of 2000, and The Denpasar Regency?s Rule No : 14 year of 2002. Before the establishment of its, the participation of traditional institution at Sumerta area in handling migrant has been done. But the authority which is possessed only in the level of controlling. After the establishment of the regency?s rules, the authority of traditional institution spread wider. The authority of traditional institutional staffs are doing controlling, coordinating, and giving information to the migrant. Next, traditional institutional staffs have an authority to give recommendation to the migrant, even though they can register as inhabitants in this area.
Keywords: traditional institution, population registration, migrant population